MENINGKATKAN MINAT DAN HASIL BELAJAR PENDIDIKAN PANCASILA MENGGUNAKAN MODEL PEMBELAJARAN SCRAMBEL DI KELAS IV SDN 186/ II KUAMANG JAYA - intan puspita sari; abdullah; refril dani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research is motivated by the low interest and learning outcomes of Pancasila Education in grade IV at SDN 186/II Kuamang Jaya, this can be seen from the results of initial observations conducted by the researcher that during the learning process there were students who were sleepy because the learning was not interactive and participatory. This has an impact on student learning outcomes, namely only 12.5% ​​who obtained grades in the achievement criteria. The purpose of the study is to increase interest and learning outcomes of Pancasila Education using the scramble learning model.The research method used in this study is classroom action research, the subjects of this study were fourth grade students of SDN 186/II Kuamang Jaya. In the implementation of the research conducted by the researcher consisted of two cycles. Each cycle consisted of two meetings, each meeting consisting of four stages: planning, implementation/action, observation, and reflection. This research was conducted in the first semester of the 2025/2026 academic year at SDN 186/II Kuamang Jaya. The research data were collected through observation, tests, and documentation.The results of the study indicate that the use of the scramble learning model can increase interest and learning outcomes of Pancasila Education in class IV of SDN 186/II Kuamang Jaya. This can be seen from the increase in the results of educator observations in cycle I with an average percentage of 78.12% and in cycle II with an average percentage of 90.62% with the Very Good category. The increase in students' learning interest, in cycle I reached 72.88% in the sufficient category and in cycle II increased to 95.8% with the Very Good category. The increase in students' learning outcomes in cycle I reached 58.3% in the Very Poor category and cycle II reached 83.3% with the Good category.